Impact of particle size and solution chemistry on ammonium elution kinetics from weathered crust elution-deposited rare earth tailings - Xiaoju Li; Junxia Yu; Zhenyue Zhang; Zhijun Li; Huicheng Li; Penghui Zhang; Yufeng Wang; Ruan Chi (Minerals Engineering, 2026)

Construction of biochar heterojunctions decorated with nanoscale zero-valent copper and CeOx for synergistically enhanced Fenton-like degradation of glyphosate - Bo Zuo; Yue Ma; Yudie Guo; Ruipu Wang; Li Guo; Shuxin Huang; Yuchi Chen; Junxia Yu (Journal of Environmental Chemical Engineering, 2026)

Two-step leaching of lead‑zinc tailings and dynamic adsorption of zinc and lead from the leachate - Zhongzheng Hu; Yan Wang; Junxia Yu; Qingbiao Zhao; Ruan Chi (Hydrometallurgy, 2026)

New insights into the temporal speciation of phosphorus during anaerobic digestion of wetland biomass wastes - Fan Yu; Junxia Wang; Zhi Wang; Lan Mu; Xutong Wang; Qianqian Guo; Xiaoqiang Cui; Yanjun Hu; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Superior adsorption of butyl xanthate by amorphization and functionalization of Ni/Fe layered double hydroxides - Jiangui Jiang; YingYing Liu; Qingbiao Zhao; Junxia Yu; Fang Zhou; Ruan Chi (Minerals Engineering, 2026)

Association of essential element mixtures with semen quality in Shanghai, China - Zhongxia Zhao; Qi Zheng; Lu He; Zhouchen Yu; Shuya Zhou; Xin Gao; Siju Chen; Junxia Liu; Yan Zhang; Linsheng Yang; Jinxia Zhai; Tailin Zhu (Environmental Toxicology and Pharmacology, 2026)

Synergistic effect of hydrodynamic cavitation and low-dose Co2+ Fenton-like reaction on Co2+/Co3+ redox cycle for the degradation of atrazine - Keqin Liu; Xinxin Zhang; Junxia Yu; Hailin Tian; Xi Yuan; Di Huang; Shichao Zhang; Yingping Huang (Journal of Water Process Engineering, 2026)

Electron bridges and electron sinks: Molecular regulation of PVC aging by aromatic plastic additives in an nZVI-driven electron-donor system - Ke Wen; Yang Xiao; Junxia Yu; Wuhui Luo; Chenao Yan; Xuan Xia; Qinhan Ye; Qianqian Yu; Jinyi Chen; Xinhong Qiu (Journal of Hazardous Materials, 2026)

Differential regulatory mechanisms of light and heavy REEs on partial nitrification in ionic rare earth tailings leachate: From hormetic responses to enzymatic suppression - Xiangyi Deng; Liqi Chai; Zhenyue Zhang; Chunqiao Xiao; Junxia Yu; Ting Zeng (Process Safety and Environmental Protection, 2026)

Degradable and non-degradable microplastics regulate soil greenhouse gas emissions: Multi-factor insights and key monitoring factors from a Kolmogorov–Arnold Network ensemble model - Chenao Yan; Yilei Cai; Ke Wen; Qianqian Yu; Xiangyang Chen; Jinyi Chen; Junxia Yu; Xinhong Qiu (Journal of Hazardous Materials, 2026)

Punicalagin alleviates enterotoxigenic Escherichia coli-induced intestinal mucosal injury via Krüppel-like factor 4 - Xiang-Guang Li; Xiaowen Zhao; Peizhi Zhu; Jibin Fu; Jiaxin Zhang; Zhixin Yu; Runting Chen; Mingxia Chen; Chuqiao Xiao; Junxia Zheng (Chemico-Biological Interactions, 2026)

Corrigendum to “Inhibition expansion mechanism of compound eluent during ammonium removal from weathered crust elution-deposited rare earth tailings” [Miner. Eng. 235 (2026) 109813] - Xiaoju Li; Junxia Yu; Peng hui Zhang; Xue fen Liu; Yun Wu; Zhenyue Zhang; Xiaodi Li; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2026)

Efficient recovery of Fe (III) from dechroming sludge with a novel combined process of acidic leaching and on-line adsorption - Chengbin Zhong; Junxia Yu; Boxi Wu; Qingbiao Zhao; Kairui Zhou; Jia Wang; Li Guo; Ruan Chi; Zhen Luo; Xiang Zhang (Journal of Environmental Chemical Engineering, 2026)

Interfacial charge-transfer–driven uptake and reduction of hexavalent chromium on amine-functionalized bentonite: mechanistic insights into surface chemistry and electron-transfer processes - Yuxin Zhang; Yulin Wang; Yifei Liu; Aoqi Li; Shuyi Yu; Yun Fang; Guowei Wang; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Journal of Environmental Management, 2026)

Decode the Ubiquitinome in Parkinson’s Disease: From Pathological Aggregates to Targeted DUB Therapeutics - Xi Yu; Qinshuai Ni; Litong Han; Shenghan Zhang; Huamin Xu; Junxia Xie; Yingjuan Liu (Neuroscience Bulletin, 2026)

Environmental and economic performance of sewage sludge-dominated organic solid waste management strategies from a life cycle perspective: co-treatment versus mono-treatment - Binbin Liu; Peng Yang; Hao Zhou; Lanfeng Li; Jing Ai; Hang He; Junxia Yu; Weijun Zhang (Resources, Conservation and Recycling, 2026)

Dual-atom catalysts on defective boron nitride for bifunctional ammonia and urea synthesis - Dongyue Gao; Lijun Shang; Junxia Li; Yadong Yu; Mengyan Dai; Yi Fang; Yang Huang; Chengchun Tang; Zhonglu Guo (Fuel, 2026)

Inhibition expansion mechanism of compound eluent during ammonium removal from weathered crust elution-deposited rare earth tailings - Xiaoju Li; Junxia Yu; Peng hui Zhang; Xue fen Liu; Yun Wu; Zhenyue Zhang; Xiaodi Li; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2026)

Revealing the phosphorus and fluorine adsorption behavior of (modified) vermiculite: Enhancing comprehensive performance in phosphogysum leachate - Fang Zhou; Xia Zhang; Chufang Liang; Bingqiao Yang; Huihua Luo; Junxia Yu; Qingbiao Zhao; Kaimin Zhang; Ruan Chi (Minerals Engineering, 2026)

Efficient recovery of chromium from electroplating sludge by a two-step roasting process: Mechanisms and kinetics - Chengbin Zhong; Junxia Yu; Boxi Wu; Jia Wang; Li Guo; Ruan Chi; Zhen Luo; YingYing Liu (Minerals Engineering, 2026)

Dosage calculation model for humic acid-enhanced in-situ leaching of weathered crust elution-deposited rare earth ores - Fang Zhou; Xia Zhang; Lisen Zhang; Kaimin Zhang; Junxia Yu; Xinyi Yang; Weiyan Yin; Ruan Chi (Minerals Engineering, 2026)

Effects of ultrasound on zein-procyanidin composite nanoparticles: Interaction force, structure, emulsifying properties and interfacial behaviors - Junxia Wang; Qiufang Liang; Mingming Zhong; Yufan Sun; Yuxuan Liu; Yongjun Zhao; Kai Yu; Arif Rashid; Abdul Qayum; Xiaofeng Ren (Food Chemistry, 2026)

An aptamer integrated electrochemistry and photoluminescence dual-mode microfluidic biosensor for sensitive and accurate ovarian cancer extracellular vesicles detection - Xiaoshuang Chen; Junxia Han; Mingyuan Sun; Zhenhua Wang; Shuai Wang; Lin Han; Yu Zhang (Analytica Chimica Acta, 2026)

Gradient elution method for treating the residual ammonium from the weathered crust elution-deposited rare earth tailings - Kejia Wu; Ruipu Wang; Jia Wang; Xiaodi Li; Yuchi Chen; Li Guo; Qingbiao Zhao; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi; Junxia Yu (Minerals Engineering, 2025)

Selective capture of Ge(IV) by chitosan functionalized with pomegranate peel polyphenol extract: Kinetic, dynamic mass transfer and mechanism insight - Hanjun Wu; Shiyin Gui; Zhenyue Zhang; Wenda Guo; Xiangyi Deng; Junxia Yu (Journal of Water Process Engineering, 2025)

Transforming glyphosate mother liquor into zirconium‑phosphorus composite adsorbent for effective Pb (II) removal from lead‑zinc tailing leachate - Bowen Dong; Ruipu Wang; Shuang Xi; Yuanping Guo; Jing Wang; Yuting Li; Li Guo; Yuchi Chen; Ruan Chi; Jia Wang; Junxia Yu (Journal of Water Process Engineering, 2025)

Prenatal exposure to environmental metal mixtures and social development in early childhood: Evidence from a birth cohort and mechanistic study - Susu Wang; Tai Ren; Yun Zhou; Chunping Hu; Xiaogang Yu; Junxia Liu; Xin Liu; Kan Shao; Yuanyuan Li; Chong-Huai Yan; Wei-Guang Li; Fei Li (Environmental Research, 2025)

Corrigendum to “Selective CP bond cleavage in glyphosate degradation via singlet oxygen-dominated alkali-activated peroxymonosulfate” [J Hazard Mater 496 (2025) 139330] - Rongrong Zhao; Honglin Liu; Danyi Chen; Di Huang; Chaojie Zhang; Haiyang Shi; Junxia Yu; Ruiping Li; Yingping Huang (Journal of Hazardous Materials, 2025)

Comprehensive evaluation of the spatiotemporal distribution characteristics of multi-source precipitation products: a case study of an extreme climate event in Henan, Central China - Zihao Pang; Junxia Gu; Yu Zhang; Yang Pan; Zheng Wang; Shuai Han; Zhi Zhu (Theoretical and Applied Climatology, 2025)

Synergistic mechanisms of plant-endophyte detoxification of Cr(VI) in phosphate mining wastelands based on 16S rDNA analysis and metabolomics - Yuxin Zhang; Aoqi Li; Ziwei Wang; Yun Fang; Guowei Wang; Junxia Yu; Ruan Chi; Chunqiao Xiao (Journal of Environmental Chemical Engineering, 2025)

Selective C−P bond cleavage in glyphosate degradation via singlet oxygen-dominated alkali-activated peroxymonosulfate - Rongrong Zhao; Honglin Liu; Danyi Chen; Di Huang; Chaojie Zhang; Haiyang Shi; Junxia Yu; Ruiping Li; Yingping Huang (Journal of Hazardous Materials, 2025)

Occurrence and microbial remediation of polycyclic aromatic hydrocarbons and heavy metals pollution in soils - Yushan Chen; Ziwei Wang; Yun Fang; Guowei Wang; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (World Journal of Microbiology and Biotechnology, 2025)

A portable instrument-assisted and dual-model sensor array with distinguished color change for the point-of-care identification of tetracycline antibiotics - Wenhao Li; Shenghao Meng; Junxia Wang; Manman Wang; Yu He (Analytica Chimica Acta, 2025)

Contrasting mediation actions on interactions of phosphorus with lanthanum modified zeolite by terrestrial- and algal-derived dissolved organic matter - Chenmin Li; Xiaodi Li; Junxia Yu; Yuanxun Zhao; Chunqiao Xiao; Fang Zhou; Ruan Chi (Journal of Environmental Management, 2025)

Reclamation of available phosphorus and separation of heavy metals from sewage sludge via FeCl3-assisted electrokinetic treatment and pyrolysis - Xutong Wang; Huwei Li; Junxia Wang; Wolfram Buss; Anna Bogush; Ondřej Mašek; Youjun Zhang; Fan Yu; Beibei Yan; Zhanjun Cheng; Xiaoqiang Cui; Guanyi Chen; et al. (Journal of Environmental Management, 2025)

A review on the production of nutrient-enriched biochar: Insights from the evolution of nitrogen, phosphorus, and potassium - Xiaoqiang Cui; Xufeng Li; Junxia Wang; Xutong Wang; Fan Yu; Gaixiu Yang; Shiwei Xu; Zhanjun Cheng; Qianying Yang; Beibei Yan; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2025)

Effect of biomass addition and plant colonization on phosphogypsum soilization: Characterization and mechanism - Hongjuan Xu; Kai Wan; Wenrui Ma; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Journal of Environmental Chemical Engineering, 2025)

Migration and transformation behaviors of phosphorus and associated elements in wet-process phosphoric acid: Acidolysis process and mechanism study - Yuanxun Zhao; Xiaodi Li; Junxia Yu; Chenmin Li; Yaoyang Ruan; Muhammad Akhtar Abbas; Ruan Chi (Journal of Environmental Chemical Engineering, 2025)

Sustainability of emerging sludge resource recovery scenarios: Process modeling and life cycle assessment - Hao Zhou; Zhiyue Wang; Binbin Liu; Hang He; Sainan Peng; Yu Zhang; Lanfeng Li; Jing Ai; Junxia Yu; Weijun Zhang (Resources, Conservation and Recycling, 2025)

Hydrogeochemical analysis and paleo-hydrogeological modeling of shallow groundwater salinization processes in North China Plain - Yihong Huang; Jie Yang; Xuan Yu; Shijie Wang; Xianjun Xie; Junxia Li; Yanxin Wang (Journal of Hydrology, 2025)

Enhancing storage stability, antihypertensive properties, flavor and functionality of fermented milk through co-fermentation with Lactobacillus helveticus H11 adjunct culture - Lu Li; Junxia Liu; Dandan Wang; Lai-Yu Kwok; Bohai Li; Shuai Guo; Yongfu Chen (Food Chemistry, 2025)

pH-regulated CQDs@Eu/GMP ICP sensor array and its fingerprinting on 96-well plates: Toward point-of-use/specific identification and quantitation of six tetracyclines in animal farm wastewater, milks and milk-derivative products - Ming Gao; Chang Bian; Junxia Wang; Yu Liu; Zhenghao Li; Yutao Zhao; Xuedong Wang (Food Chemistry, 2025)

Fatty acid binding protein 4 regulates doxorubicin-induced renal injury via mediating lipid metabolism and apoptosis - Chuchu Wang; Tao Zhang; Yufeng Guan; Boye Han; Shang Wu; Xu Wang; Jing Yu; Junxia Zhang; Guoqiang Zhang; Qingfeng Miao; Suwen Su (Chemico-Biological Interactions, 2025)

Ultrafiltration membrane fouling of microalgae-derived intracellular organic matter exposed to pharmaceuticals and personal care products (PPCPs) - Weiwei Huang; Hongkai Xu; Lei Yao; Tian Li; Yongting Qiu; Hongjian Yu; Huan He; Chunzhong Wei; Junxia Liu; Wenzong Zhou; Bingzhi Dong; Bing Wu (Journal of Water Process Engineering, 2025)

Enhanced Pb immobilization by CaO/MgO-modified soybean residue (okara) in phosphate mining wasteland soil: Mechanism and microbial community structure - Ziwei Wang; Mengting Huang; Yuxin Zhang; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Journal of Environmental Management, 2025)

Recycle of residual ammonium from weathered crust elution-deposited rare earth tailings via an efficient combined method of elution, struvite precipitation and on-line adsorption - Kejia Wu; Junxia Yu; Jia Wang; Xiaodi Li; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Journal of Water Process Engineering, 2024)

Efficient removal of chromium from electroplating sludge by a novel combined process of alkaline oxidizing roasting, water leaching and on-line adsorption - Chengbin Zhong; Junxia Yu; Jia Wang; Xiaodi Li; Li Guo; Ruan Chi; Yuchi Chen; Yue Chen (Journal of Environmental Chemical Engineering, 2024)

Magnesium polypeptide combined with microbially induced calcite precipitation for remediation of lead contamination in phosphate mining wasteland soil - Ziwei Wang; Ziyue Zhang; Jun Peng; Yuxin Zhang; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Environmental Research, 2024)

Anxiety caused by chronic exposure to methylisothiazolinone in zebrafish: Behavioral analysis, brain histology and gene responses - Rui Li; Jiangbo Qu; Xinyuan Hu; Tianjia Song; Junxia Hu; Xuesong Fan; Yuanqing Zhang; Weili Xia; Tiangui Yu (Chemosphere, 2024)

Efficient reclamation of phosphorus from wetland biomass waste via liquid-recirculated hydrothermal carbonization and precipitation - Junxia Wang; Yuting Wang; Fan Yu; Jiangtao Wang; Xutong Wang; Jipeng Luo; Chao He; Xiaoqiang Cui; Beibei Yan; Guanyi Chen (Water Research, 2024)

Regional heterogeneity of sustainable wastewater sludge management in China - Hao Zhou; Zhiyue Wang; Binbin Liu; Hang He; Sainan Peng; Yu Zhang; Lanfeng Li; Jing Ai; Junxia Yu; Weijun Zhang (Resources, Conservation and Recycling, 2024)

Efficient removal of phosphate and fluoride from phosphogypsum leachate by lanthanum-modified zeolite: Synchronous adsorption behavior and mechanism - Mengxuan Zhao; Xiaomeng Zhou; Junfeng Li; Fei Li; Xiaodi Li; Junxia Yu; Li Guo; Guoping Song; Chunqiao Xiao; Fang Zhou; Ruan Chi; Guoqing Feng (Journal of Environmental Chemical Engineering, 2024)

Heterotrophic nitrification processes driven by glucose and sodium acetate: New insights into microbial communities, functional genes and nitrogen metabolism from metagenomics and metabolomics - Jingang Hu; Jiaoyang Tian; Xiangyi Deng; Xuemei Liu; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Bioresource Technology, 2024)

Polymerase chain reaction-based methods for the rapid identification of Amanita exitialis - Yu Zhang; Shuifang Zhu; Chaonan Wang; Junxia Shi; Jiayao He; Jian Chen; Liang Liang; Fan Jiang (Food Chemistry, 2024)

Efficient removal of the residual ammonium from weathered crust elution-deposited rare earth tailings by a ternary compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Rong Wang; Fang Zhou; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2024)

Phosphorus immobilization/release behavior of lanthanum-modified bentonite amended sediment under the dual effects of pH and dissolved organic carbon - Xiaodi Li; Xiaomeng Zhou; Junxia Yu; Chunqiao Xiao; Ruan Chi (Chemosphere, 2024)

Eliminating waste with waste: Removal of doxycycline in water by goethite modified phosphogypsum - Meng Lu; Yao Wang; Wenxin Jiao; Junxia Yu; Peng Gao; Qingbiao Zhao; Dezeng Li; Ruan Chi (Journal of Water Process Engineering, 2024)

Molecular insights into effects of chemical conditioning on dissolved organic phosphorus transformation and bioavailability during sludge composting - Boyuan Yang; Yu Zhang; Zexu Chen; Peng Yang; Siwei Peng; Junxia Yu; Dongsheng Wang; Weijun Zhang (Bioresource Technology, 2024)

Preparation of Biofertilizer with Phosphogypsum and Straw: Microbial Community Changes and Plant Growth Effects - Yongtong Jin; Dan Yang; Yuehong Wu; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Journal of Soil Science and Plant Nutrition, 2024)

Mechanistic insights into chemical conditioning on transformation of dissolved organic matter and plant biostimulants production during sludge aerobic composting - Yu Zhang; Boyuan Yang; Siwei Peng; Ziwei Zhang; Siying Cai; Junxia Yu; Dongsheng Wang; Weijun Zhang (Water Research, 2024)

Mechanistic investigation of Pb2+ adsorption on biochar modified with sodium alginate composite zeolitic imidazolate framework-8 - Jun Peng; Qian Xiao; Ziwei Wang; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Environmental Science and Pollution Research, 2024)

Inhibitory effect of microplastics derived organic matters on humification reaction of organics in sewage sludge under alkali-hydrothermal treatment - Jun Chen; Tong Sun; Peng Yang; Siwei Peng; Junxia Yu; Dongsheng Wang; Weijun Zhang (Water Research, 2024)

Collision-attachment simulation of membrane fouling by oppositely and similarly charged colloids - Wen Sun; Hangfan Zhou; Xuri Yu; Dongsheng Zhao; Junxia Liu; Linchun Chen; Zhihong Wang; Guicai Liu; Yongting Qiu; Yaoliang Hong (Water Research, 2024)

Interaction of prenatal maternal selenium and manganese levels on child neurodevelopmental trajectories-the Shanghai birth cohort study - Xiangrong Guo; Jian Xu; Ying Tian; Fengxiu Ouyang; Xiaodan Yu; Junxia Liu; Chonghuai Yan; Jun Zhang (Science of The Total Environment, 2024)

Double-edged effect of frequent freeze-thaw on the stability of zero-valent iron after heavy metal remediation - Xiaoxuan Zhang; Jialing Zhao; Qianqian Yu; Jinyi Chen; Junxia Yu; Zhanqiang Fang; Xinhong Qiu (Journal of Hazardous Materials, 2024)

Comparison of microbial communities in unleached and leached ionic rare earth mines - Lingyan Li; Haitao Wang; Jingang Hu; Yun Fang; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Environmental Science and Pollution Research, 2024)

Metagenomic analysis revealed the evolution of microbial communities, metabolic pathways, and functional genes in the heterotrophic nitrification-aerobic denitrification process under La3+ stress - Jingang Hu; Kai Wan; Xiangyi Deng; Xuemei Liu; Yun Fang; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Science of The Total Environment, 2024)

Coupling electrokinetic technique with hydrothermal carbonization for phosphorus-enriched hydrochar production and heavy metal separation from sewage sludge - Xutong Wang; Ondřej Mašek; Huwei Li; Fan Yu; Christian Wurzer; Junxia Wang; Beibei Yan; Xiaoqiang Cui; Guanyi Chen; Li'an Hou (Chemical Engineering Journal, 2024)

Molecular transformation pathway and bioavailability of organic phosphorus in sewage sludge under vermicomposting - Hao Yuan; Yu Zhang; Zexu Chen; Siying Cai; Ziwei Zhang; Peng Yang; Siwei Peng; Junxia Yu; Dongsheng Wang; Weijun Zhang (Science of The Total Environment, 2024)

Environmental impact and optimization suggestions of pig manure and wastewater treatment systems from a life cycle perspective - Binbin Liu; Hao Zhou; Lanfeng Li; Jing Ai; Hang He; Junxia Yu; Ping Li; Weijun Zhang (Science of The Total Environment, 2023)

Synergistic leaching process for ion-exchange ammonium from weathered crust elution deposited rare earth tailings with potassium magnesium compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Guoping Song; Ze Ouyang; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Environmental Science and Pollution Research, 2023)

Mechanisms of combined bioremediation by phosphate-solubilizing fungus and plants and its effects on cadmium contamination in phosphate-mining wastelands - Ziwei Wang; Yunting Zheng; Jun Peng; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Journal of Environmental Management, 2023)

Treating waste with waste: Adsorption of anionic dyes in wastewater with surfactant-modified phosphogypsum - Meng Lu; Yao Wang; Junxia Yu; Dezeng Li; Qingbiao Zhao; Ruan Chi (Environmental Research, 2023)

Comparative analysis of helium and air surface micro-discharge plasma treatment on the microbial reduction and quality attributes of beef slices - Hangbo Xu; Yupan Zhu; Bo Yu; Mengru Du; Junxia Feng; Jie Zhuang; Ruonan Ma; Zhen Jiao (Meat Science, 2023)

Recyclable and reusable layered double hydroxide beads for soil remediation: Conveying belt recovery model, mechanism, bioavailability and microbial communities - Zhenhui Li; Yuqi Jing; Xiaoxuan Zhang; Rongjie Zhu; Junxia Yu; Jinyi Chen; Xinhong Qiu (Journal of Environmental Chemical Engineering, 2023)

A multi-dimensional relationship assessment framework for water resources, social economy and eco-environment: A case study of China's largest arid zone - Jiawei Li; Qiting Zuo; Lei Yu; Junxia Ma (Environmental Impact Assessment Review, 2023)

Performance changes in the anammox process under the stress of rare-earth element Ce(III) and the evolution of microbial community and functional genes - Chunqiao Xiao; Kai Wan; Jinggang Hu; Xiangyi Deng; Xuemei Liu; Fang Zhou; Junxia Yu; Ruan Chi (Bioresource Technology, 2023)

Biofuel production by hydro-thermal liquefaction of municipal solid waste: Process characterization and optimization - Dongmin Yu; Jing Guo; Junxia Meng; Tianyi Sun (Chemosphere, 2023)

The influence of various microplastics on PBDEs contaminated soil remediation by nZVI and sulfide-nZVI: Impedance, electron-accepting/-donating capacity and aging - Xiaoxuan Zhang; Ran Chen; Zhenhui Li; Junxia Yu; Jinyi Chen; Yuanyuan Zhang; Jinhong Chen; Qianqian Yu; Xinhong Qiu (Science of The Total Environment, 2023)

Elution of the residual water-soluble ammonium from the weathered crust elution-deposited rare earth tailings: Kinetics and mechanism - Xiaoju Li; Ze Ouyang; Zhanhui Li; Junxia Yu; Zhenyue Zhang; Xiaodi Li; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2023)

Carbon nitride-type polymers compounded with FeOCl to enhance the catalytic removal of antibiotics over a wide pH range: Performance and mechanism - Yu Jiang; Kang Mao; Jiabing Ran; Junxia Su; Guopei Huang; Xingli Zheng; Kuankuan Zhang; Hui Guan; Changying Yang; Hua Zhang (Journal of Water Process Engineering, 2023)

Relating critical and limiting fluxes to metastable and long-term stable fluxes in colloidal membrane filtration through collision-attachment theory - Junxia Liu; Wei Fu; Xuri Yu; Haiyan Yang; Dongsheng Zhao; Zhihong Wang; Lin Wang; Xianhui Li; Chuyang Y. Tang (Water Research, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Carbon quantum dots (CQDs) mediated Z-scheme g–C3N4–CQDs/BiVO4 heterojunction with enhanced visible light photocatalytic degradation of Paraben - Maosheng Tian; Chenyan Hu; Junxia Yu; Lianguo Chen (Chemosphere, 2023)

Ferrihydrite-loaded water hyacinth-derived biochar for efficient removal of glyphosate from aqueous solution - Wenchao Meng; Xiaodi Li; Junxia Yu; Chunqiao Xiao; Haobo Hou; Ruan Chi; Guoqing Feng (Environmental Science and Pollution Research, 2023)

Natural variations of OsAUX5, a target gene of OsWRKY78, control the neutral essential amino acid content in rice grains - Yuheng Shi; Yuanyuan Zhang; Yangyang Sun; Ziyang Xie; Yu Luo; Qiyuan Long; Jiahui Feng; Xueqing Liu; Bi Wang; Dujun He; Junxia Ren; Peizhen Guo; et al. (Molecular Plant, 2023)

A combined precipitation-adsorption method for harmless treatment of glyphosate mother liquor - Zhanhui Li; Yi Wang; Ruyi Zhou; Junxia Yu; Xiaodi Li; Chunqiao Xiao; Haobo Hou; Ruan Chi; Guoqing Feng (Journal of Cleaner Production, 2023)

Real-time and rapid prediction of TVB-N of livestock and poultry meat at three depths for freshness evaluation using a portable fluorescent film sensor - Duoduo Zhang; Li Zhu; Qingwei Jiang; Xinyu Ge; Yu Fang; Junxia Peng; Yongfeng Liu (Food Chemistry, 2023)

Effect of calcination temperatures on the performance of rectorite for cadmium immobilization in soil: Freeze-thaw, plant growth, and microbial diversity - Xing Fang; Wenying Yuan; Zhenhui Li; Xiaoxuan Zhang; Junxia Yu; Jinyi Chen; Xiaofeng Wang; Xinhong Qiu (Environmental Research, 2023)

A coupled molybdenum disulfide - copper modification of NF membrane for enhanced anti-bacterial performance - Junxia Liu; Pei Cao; Xuri Yu; Tian Li; Wen Sun; Yaxiang Zhao; Hongjian Yu; Zhihong Wang; Jialuo Zeng; Bingzhi Dong; Haiyan Yang; Shuili Yu (Desalination, 2023)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Expanding Views of Mitochondria in Parkinson’s Disease: Focusing on PINK1 and GBA1 Mutations - Yu Yuan; Xizhen Ma; Ning Song; Junxia Xie (Neuroscience Bulletin, 2022)

Desferrioxamine Ameliorates Lipopolysaccharide-Induced Lipocalin-2 Upregulation via Autophagy Activation in Primary Astrocytes - Juntao Cui; Yu Yuan; Jun Wang; Ning Song; Junxia Xie (Molecular Neurobiology, 2022)

miR-874-3p mitigates cisplatin resistance through modulating NF-κB/inhibitor of apoptosis protein signaling pathway in epithelial ovarian cancer cells - Ying Wang; Chenming Yan; Junxia Qi; Chunyan Liu; Juan Yu; Huabin Wang (Molecular and Cellular Biochemistry, 2022)

New Insights into the Role of Ferritin in Iron Homeostasis and Neurodegenerative Diseases - Na Zhang; Xiaoqi Yu; Junxia Xie; Huamin Xu (Molecular Neurobiology, 2021)

Chlorobenzenes Contamination in Soils/Sediments at a Site of Decommissioned Plant in Central China - Mei Yu; Zejiao Luo; Yanxin Wang; Junxia Li (Journal of Earth Science, 2018)

A two-step leaching method designed based on chemical fraction distribution of the heavy metals for selective leaching of Cd, Zn, Cu, and Pb from metallurgical sludge - Fen Wang; Junxia Yu; Wanli Xiong; Yuanlai Xu; Ru-an Chi (Environmental Science and Pollution Research, 2018)

Monitoring and modeling the effects of groundwater flow on arsenic transport in Datong Basin - Qian Yu; Yanxin Wang; Rui Ma; Chunli Su; Ya Wu; Junxia Li (Journal of Earth Science, 2014)

Improvement of expression level of keratinase Sfp2 from Streptomyces fradiae by site-directed mutagenesis of its N-terminal pro-sequence - Junxia Li; Dongdong Chen; Zhanqiao Yu; Longmei Zhao; Rijun Zhang (Biotechnology Letters, 2013)

Nuclear Translocation of β-catenin is Essential for Glioma Cell Survival - Zhendong Shi; Xiaomin Qian; Lanquan Li; Junxia Zhang; Shanjun Zhu; Jialin Zhu; Luyue Chen; Kailiang Zhang; Lei Han; Shizhu Yu; Peiyu Pu; Tao Jiang; et al. (Journal of Neuroimmune Pharmacology, 2012)

Nifedipine Prevents Iron Accumulation and Reverses Iron-Overload-Induced Dopamine Neuron Degeneration in the Substantia Nigra of Rats - ZeGang Ma; Yu Zhou; JunXia Xie (Neurotoxicity Research, 2012)

Identification of Aspergillus section Flavi in maize in northeastern China - Junxia Gao; Zuoxin Liu; Jiujiang Yu (Mycopathologia, 2007)